1996
DOI: 10.1088/0022-3727/29/8/002
|View full text |Cite
|
Sign up to set email alerts
|

The luminescence of sapphire subjected to the irradiation of energetic hydrogen and helium ions

Abstract: The luminescence of during and irradiation was measured in the 190 - 820 nm wavelength range. The luminescence evolution with the ion fluence exhibits two behaviours : (i) at low fluence, the amount of centres increases; (ii) at high fluences, these defects are completely (F centres) or partially ( centres) annihilated. This phenomenon results from two concomittant mechanisms : a conversion between F and defects and a destruction of both luminescent species resulting from the radiation-induced damage. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…Therefore, even though some luminescence of the sapphire was detected under the ion beam, it is many orders of magnitude lower than that under the electron beam from the GaN in this sample. Luminescence of sapphire, excited via electrons (CL) (Miyauchi & Shibata, 1993) or He ions (IL) (Jardin et al, 1996), has been studied previously. Jardin et al have reported strong IL emission of a sapphire sample when irradiated with a 2 MeV He + beam (Jardin et al, 1996).…”
Section: Direct Bad Gap Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, even though some luminescence of the sapphire was detected under the ion beam, it is many orders of magnitude lower than that under the electron beam from the GaN in this sample. Luminescence of sapphire, excited via electrons (CL) (Miyauchi & Shibata, 1993) or He ions (IL) (Jardin et al, 1996), has been studied previously. Jardin et al have reported strong IL emission of a sapphire sample when irradiated with a 2 MeV He + beam (Jardin et al, 1996).…”
Section: Direct Bad Gap Semiconductorsmentioning
confidence: 99%
“…Luminescence of sapphire, excited via electrons (CL) (Miyauchi & Shibata, 1993) or He ions (IL) (Jardin et al, 1996), has been studied previously. Jardin et al have reported strong IL emission of a sapphire sample when irradiated with a 2 MeV He + beam (Jardin et al, 1996). The IL intensity initially increases with increasing ion dose due to creation of defects that act as F + centres.…”
Section: Direct Bad Gap Semiconductorsmentioning
confidence: 99%
“…As expected it exhibits luminescence around 415 nm. However, the by far strongest peak at 330 nm corresponds to the emission of F + -centers [164,165]. An F -center in sapphire (Al 2 O 3 ) consists of two electrons, which occupy an oxygen vacancy.…”
Section: Bulk Semiconductorsmentioning
confidence: 99%
“…An F -center in sapphire (Al 2 O 3 ) consists of two electrons, which occupy an oxygen vacancy. Under irradiation an F-center can lose an electron and is converted into an F + -center [164,165]. A small sharp peak at ∼695 nm originates from the impurity Cr 3+ ions [165,166].…”
Section: Bulk Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation